A superstructure model of an isolated power supply system using renewable energy: Development and application to Jeju Island, Korea. (November 2016) - Kwon, Sunghoon; Won, Wangyun; Kim, Jiyong
Abstract: In this study, we aim to develop a superstructure-based optimization model using mixed integer linear programming (MILP) to determine the optimal combination and sizing for a hybrid renewable energy system to be used in an isolated area. The developed model has a three-layered energy structure to reflect the current reality in which energy production and consumption sites are generally separate. A variety of economic factors, including distance between facilities and an installation area, are considered for a more accurate estimation of the total annualized cost. Two types of optimization models, i.e., with and without a battery, are proposed to evaluate the economic and technical effects of a storage device to resolve operation issues caused by intermittent resources. An application case study on Jeju Island, Korea, confirms that the proposed model is suitable for decision making at the planning stage of a renewable energy system. Highlights: A superstructure model of isolated power supply system using renewable energy. The model has three-layered energy structure. Two-types of model, i.e. with and without battery, is developed. Diverse energy sources and various economic factors are considered. The proposed model was validated through application to Jeju Island, Korea.